2020
DOI: 10.3390/pharmaceutics12100993
|View full text |Cite
|
Sign up to set email alerts
|

Increased Carrier Peptide Stability through pH Adjustment Improves Insulin and PTH(1-34) Delivery In Vitro and In Vivo Rather than by Enforced Carrier Peptide-Cargo Complexation

Abstract: Oral delivery of therapeutic peptides is hampered by their large molecular size and labile nature, thus limiting their permeation across the intestinal epithelium. Promising approaches to overcome the latter include co-administration with carrier peptides. In this study, the cell-penetrating peptide penetratin was employed to investigate effects of co-administration with insulin and the pharmacologically active part of parathyroid hormone (PTH(1-34)) at pH 5, 6.5, and 7.4 with respect to complexation, enzymati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 37 publications
1
10
0
Order By: Relevance
“…Moreover, L-penetratin has previously been observed to associate with insulin at the investigated pH although at lower concentrations. 24 In relation to the higher insulin P app values when in the presence of shuffle and penetramax compared to when in the presence of penetratin (Figure 3C), insulin complexation appeared to influence the enhancing effect of the carrier peptides. Insulin was used as a model cargo in the present study, and naturally, the degree of peptide interactions with the cargo will depend on their physiochemical properties such as charge of the cargo, and thus, the enhancing effect will depend on the cargo as demonstrated with other therapeutic peptides.…”
Section: ■ Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…Moreover, L-penetratin has previously been observed to associate with insulin at the investigated pH although at lower concentrations. 24 In relation to the higher insulin P app values when in the presence of shuffle and penetramax compared to when in the presence of penetratin (Figure 3C), insulin complexation appeared to influence the enhancing effect of the carrier peptides. Insulin was used as a model cargo in the present study, and naturally, the degree of peptide interactions with the cargo will depend on their physiochemical properties such as charge of the cargo, and thus, the enhancing effect will depend on the cargo as demonstrated with other therapeutic peptides.…”
Section: ■ Discussionmentioning
confidence: 85%
“…This is consistent with the lack of a linear combination for mixtures with l -penetratin (Figure S3), suggesting some complex formation despite the lack of a distinct increase at low q (<0.03 Å –1 ), indicative of aggregation (Figure A). Moreover, l -penetratin has previously been observed to associate with insulin at the investigated pH although at lower concentrations …”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Tat and Penetratin are among the most studied CPPs, which have been employed as a vector to improve intracellular delivery of various drug compounds, including oligonucleotides ( Brown & Graham, 2010 ) and proteins ( Harada et al, 2002 ; Liang & Yang, 2005 ; Kamei et al, 2008 ; Khafagy et al, 2009 ). Besides that, both Tat and Penetratin have been shown to promote permeation through tight junction modulation ( Bai et al, 2008 ; Kristensen et al, 2020 ; Diedrichsen et al, 2021 ). However, results from our study showed that Tat and Penetratin had no permeabilizing effect in the Caco-2 monolayer setup at 100 µM.…”
Section: Discussionmentioning
confidence: 99%
“…Paracellular spaces are aqueous filled channels through which these drugs prefer to diffuse ( Salamat-Miller and Johnston, 2005 ; Patel and Misra, 2011 ). Several studies have reported that some CPPs can also promote permeation of various cellular barriers through paracellular route both in vitro and in vivo ( Ohtake et al, 2002 ; Bai et al, 2008 ; Kristensen and Nielsen, 2016a ; Kristensen and Nielsen, 2016b ; Kristensen et al, 2020 ; Diedrichsen et al, 2021 ; Ragupathy et al, 2021 ; Frøslev et al, 2022 ). This could be either due to the high local concentration of the CPPs, influencing the dynamics of the tight junction proteins or due to cell-penetrating tendency of CPPs, targeting intracellular proteins which are involved in regulation of opening and closing of tight junctions ( Taverner et al, 2015 ; Kristensen and Nielsen, 2016a ).…”
Section: Introductionmentioning
confidence: 99%